1993
DOI: 10.1002/eji.1830230114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of activation‐induced changes in the structure of the T cell interleukin‐7 receptor by cyclosporin A and FK506

Abstract: We have recently shown that activation of T cells causes structural changes in the interleukin-7 receptor (IL-7R) (Foxwell et al. Int. Immunol. 1992, 4: 277). Unactivated cells expressed a receptor characterized as a cross-linked protein of 107-kDa whereas activated cells had reduced levels of this 107-kDa complex and now express a major cross-linked product of 93 kDa. These changes in receptor expression were concomitant with the acquisition of IL-7 growth responsiveness by activated T cells. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Itnmunoprecipitation studies and imtnunostaining of patticular T cell clones, which mainly express the p76 IL-7R, demonstrated that p76 kDa IL-7R is immunologically distinct from the p90 IL-7R (18), stiggesting that the p76 IL-7R is likely to be a product from a distinct gene. Activation of peripheral blood mononuclear cells (PBMC) in the ptesence of cyclosporin A or FK 506, which both inhibit IL-7-induced proliferation, repressed the expression of tbe p76 IL-7R but does not affect expression ofthe p90 IL-7R (19), These data imply that expression ofthe p76 1L-7R is necessary for IL-7-driven proliferation. The function of the ultra-low IL-7 receptor, which seetns to be a distinct entity, is currently unknown (15).…”
Section: Characterization Of Il-7 and Its Receptormentioning
confidence: 94%
“…Itnmunoprecipitation studies and imtnunostaining of patticular T cell clones, which mainly express the p76 IL-7R, demonstrated that p76 kDa IL-7R is immunologically distinct from the p90 IL-7R (18), stiggesting that the p76 IL-7R is likely to be a product from a distinct gene. Activation of peripheral blood mononuclear cells (PBMC) in the ptesence of cyclosporin A or FK 506, which both inhibit IL-7-induced proliferation, repressed the expression of tbe p76 IL-7R but does not affect expression ofthe p90 IL-7R (19), These data imply that expression ofthe p76 1L-7R is necessary for IL-7-driven proliferation. The function of the ultra-low IL-7 receptor, which seetns to be a distinct entity, is currently unknown (15).…”
Section: Characterization Of Il-7 and Its Receptormentioning
confidence: 94%
“…7 Full-length human IL-7R has an expected molecular weight of 90 kd in reducing SDS-PAGE. 8 A 90-kd band of IL-7R was detected in HS-27a, primary LTCs of bone marrow, and PBMCs ( Figure 3A). However, immunoblotting for IL-7R protein in whole cell extracts of HS-27a occasionally revealed a smaller 30-kd band.…”
Section: Il-7r Protein Expression Correlates With Il-7r Gene Expressionmentioning
confidence: 99%